Nigeria's Foreign Policy and Foreign Goodwill in the Fourth Republic, 1999-2022: An Appraisal - Saleh, Bailey (Kashere Journal of Politics and International Relations, 2023)
With the enthronement of civil democratic governance in Nigeria's political environment Won May 29, 1999 to date (2023), successive administrations of the Fourth Republic have on sustainable basis, been pursuing deliberate foreign policy of image laundering and rapprochement; as well as of maintaining friendship with all countries and international organizations. They adopted a deliberate foreign policy instrument of 'wandering around' or “shuttle diplomacy” to convince the comity of nations that with the enthronement and consolidation of democracy in the country, Nigeria's domestic environment is now safe and clean for doing business. Their efforts paid off when foreign goodwill started flowing into Nigeria from friendly western and eastern countries; as well as international economic organizations and private nongovernmental organizations. The study is therefore embarked upon to unearth these loopholes and proffer workable solutions towards netting-in more foreign goodwill and of directing it towards industrialization and manufacturing. The study is a qualitative one where secondary sources of data such as academic journals, textbooks, online sources, newspapers and magazines were scrutinized for generating data. At the end recommendations were made; principal among which is the need for government to encourage Nigeria's benefactors to direct most of their donations, grants, assistance to growing the country's industrial and manufacturing sector/subsector that will generate more employment and economically empowers majority of the citizens.